A step-by-step guide to design and delivery of mobile learning content. - Gabarre, Serge; Gabarre, Cecile (IGI Global, 2012)
Mobile learning is more than a trend that follows today’s lifestyle. Learning on the go with mobile internet offers advantages that were not even thought of a few years ago. Current literature on the topic has demonstrated its usefulness as well as its limitations. In a context where learners do not have access to mobile internet it is still possible to deliver course notes in a mobile format. The authors created portable lecture notes that were distributed to their students via the multimedia messaging service (MMS). With these notes, the students were able to take advantage of the ubiquitous nature of their mobile devices and thus started to learn anywhere and anytime. This chapter proposes a simple method to create lecture notes for mobile devices and suggests several methods of delivery.